Immunopathophysiology of Juvenile Spondyloarthritis (jSpA): The “Out of the Box” View on Epigenetics, Neuroendocrine Pathways and Role of the Macrophage Migration Inhibitory Factor (MIF) - Harjacek, Miroslav (Frontiers in Medicine, 2021)
Juvenile spondyloarthritis (jSpA) is a heterogeneous group of related seronegative inflammatory disorders with shared symptoms. Although it mainly affects children and adolescents, it often remains active during adulthood. Genetic and environmental factors are involved in its occurrence, although the exact underlying immunopathophysiology remains incompletely elucidated. Emerging evidence suggests that, in affected patients, subclinical gut inflammation, driven by intestinal dysbiosis, is pivotal to the future development of synovial–entheseal complex inflammation. While the predominant role of IL17/23 axis, TNF-𝛼, and IL-7 in the pathophysiology of SpA, including jSpA, is firmly established, the role of the cytokine macrophage migration inhibitory factor (MIF) is generally overlooked. The purpose of this review is to discuss and emphasize the role of epigenetics, neuroendocrine pathways and the hypothalamic-pituitary (HPA) axis, and to propose the hypothesis of the role of decreased NLRP3 gene expression and possibly MIF in the early phases of jSpA development. In addition, the complex innate and adaptive cellular and main effector cytokine network, the role of MIF in those interactions is highlighted. Finally, since treatment of the bone pathology in SpA remains an unmet clinical need, I suggest possible new drug targets with the aim to ultimately improve treatment efficacy and long-term outcome of jSpA patients.